The morphing of decay powered to interaction powered Type II supernova ejecta at nebular times - Dessart Luc; Gutierrez Claudia P; Kuncarayakti Hanindyo; Fox Ori D; Filippenko Alexei V (EDP SCIENCES S A, 2025)
There is significant astronomical interest around the intense mass loss that appears to take place in some massive stars immediately before core collapse. However, because it occurs too late, it has a negligible impact on the star's evolution or the final yields. These properties are then influenced instead by the longer term, quasi-steady, and relatively weak mass loss taking place during H and He burning. Late-time observations of core-collapse supernovae (SNe) interacting with the progenitor wind are one means of constraining this secular mass loss. Here, we present radiative transfer calculations for a Type II SN from a standard red-supergiant (RSG) star explosion. At first, a reference model was computed without interaction power. A second model was then taken to assume a constant interaction power of 1040 erg s-1 associated with a typical RSG progenitor wind mass-loss rate of 10-6 M⊙yr-1. We focused on the phase between 350 and 1000 d after explosion. We find that without interaction power, the ejecta are powered through radioactive decay, whose exponential decline produces an ever-fading SN. Instead, with a constant interaction power of 1040 erg s-1, the spectrum morphs from decay powered at 350 d, with narrow lines forming in the inner metal-rich ejecta, to interaction powered at 1000 d, with broad boxy lines forming in the outer H-rich ejecta. Intermediate times are characterized by a hybrid and complex spectrum made of overlapping narrow and broad lines. While interaction boosts primarily the flux in the ultraviolet, which remains largely unobserved today, a knee in the R-band light curve or a U-band boost are clear signatures of interaction at late times. The model predictions offer a favorable comparison with a number of Type II SNe, including SN 2004et or SN 2017eaw at 500-1000 d after explosion.